The Implementation of Environment-Based Madrasah Culture in Islamic Religious Education Learning to Develop Students’ Character - Pristine Adi, Depict; Mashudi, Mashudi; Fauziah, Nahdiah Nur; Minasyan, Sona (Universitas Muhammadiyah Magelang, 2024)
Islamic Education that has important roles in developing student character in Indonesia aims to create high moral individuals who are able to positively contribute to the community. This research evaluates the implementation of environment-based madrasah cultures at MIN 1 Banyuwangi and the impact on student character development. Qualitative research method is used with data collection technique that includes interview, observation, and document analyses. The research results show that environment-based madrasah cultures at MIN 1 Banyuwangi have succeeded in developing students’ characters of environmental caring, responsible, discipline, creative and independence. Integration of culture with Islamic Religious Education learning has also proven effective in instilling moral and spiritual values ​​in students. In conclusion, the implementation of an environment-based madrasah culture can be an effective strategy in forming quality and environmentally aware student characters.